Psychological Distress Across Grade Levels in Cadet-Based Boarding Senior High School Students: A Comparative Study of Depression, Anxiety, and Stress - Diniy Hidayatur Rahman; Zamroni Zamroni; Afifah Army Age (Indonesian Journal of Counseling and Development, 2026)
This study evaluated differences in depression, anxiety, and stress across grade levels among students in a cadet-based boarding senior high school. The study employed a quantitative approach with a comparative design, involving 423 students from grades X, XI, and XII, with an equal distribution of respondents across each grade. Data were collected using the 42-item Depression Anxiety Stress Scales (DASS-42) to measure the three psychological dimensions. Data analysis was conducted using descriptive statistics and group comparison tests, specifically applying analysis of variance (ANOVA) and Welch tests based on data distribution characteristics, followed by the Games-Howell post hoc test for variables demonstrating significant variations. The findings revealed that grade-level differences emerged exclusively for depression. Grade XI students reported higher mean depression scores (M = 6.45, SD = 7.73) than grade X students (M = 4.35, SD = 5.62), as indicated by Welch’s F (2, 275.7) = 3.62, p = .028, with the Games–Howell test confirming a significant difference between grade X and grade XI (p = .027). Anxiety and stress did not differ significantly across grade levels. Across all grades, group mean scores for the three dimensions remained within the normal-to-mild ranges of the DASS-42 norms. This study concludes that student mental health dimensions in a cadet-based boarding school environment do not develop uniformly across grade levels. Consequently, guidance and counseling services must strengthen promotive and preventive initiatives that are highly responsive to students' specific developmental phases, particularly focusing on monitoring depressive symptoms among more vulnerable student groups.